Identification of uncorrelated sources of exciting forces by means of the methods of crosspower spectrum matrix decomposition into singular values and eigenvalues - KROMULSKI, J. (Archives of Acoustics, 1998)
The practical use of the method of the crosspower spectrum matrix decomposition into singular values in problems of the identification of exciting force sources is discussed. These methods were used to identify the sources of the exciting forces acting during the work of a real mechanical system - a collecting press of high level crushing. The method allowed to draw conclusions about the number of uncorrelated exciting forces acting in the system and the points of the exciting force application.